Extractives Contributing to the Color of Swietenia macrophylla King Bark - Masendra Masendra; Rizki Arisandi; Brandon Aristo Verick Purba; Fuad Sumantri; Fatra Valahatul Ihda; Fatimah Zulaikha Wati; Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2020)
The bark of Swietenia machrophylla is colored dark red, and it is correlated with the extractives constituents such as phenolic compounds. This study, therefore, aims to investigate extractives from the inner and outer bark of S. machrophylla and their effects to color properties. The results showed that the extractive content in the inner bark was higher than the outer except for hot water solubles. In addition, the polyphenols and sugar levels from inner to outer bark were increased, except in the soluble-sugar of hot water extractive. The highest correlation between the absorbance of methanol, hot water-soluble extracts, and total polyphenols were observed using the visual spectrophotometer. The extractives that contributed to the bark's color were indicated from flavonoids with a precursor such as monophenol of catechol and resorcinol.